2008
DOI: 10.1007/s00405-008-0836-0
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative application of amphotericin B nasal spray in chronic rhinosinusitis with nasal polyposis, with a review of the antifungal therapy

Abstract: Chronic rhinosinusitis (CRS) affects 1-4% of the adult population. The etiology of this multifactorial, chronic disease, which leads to a significant impairment of the quality of life, often accompanied by nasal polyposis, is not fully understood. In the past decade, it was presumed that the disease, which causes characteristic eosinophilic infiltration of the nasal mucosa, is triggered by an enhanced (but not classical allergic IgE-type) immune response against fungal organisms in the nasal mucus. If this sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…Nasal Endoscopy Scores. For nasal endoscopy scores, data from four trials were pooled for meta-analysis, [35][36][37][38] with 101 patients allocated to topical antifungals and 103 patients allocated to placebo. Weschta et al did not consider endoscopy scores in their outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasal Endoscopy Scores. For nasal endoscopy scores, data from four trials were pooled for meta-analysis, [35][36][37][38] with 101 patients allocated to topical antifungals and 103 patients allocated to placebo. Weschta et al did not consider endoscopy scores in their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…40 Four trials (66.7%) had both adequate sequence generation and allocation concealment as ascertained from the articles or by correspondence. [35][36][37][38] One trial (16.7%) had adequate sequence generation but no information was given regarding the method of allocation concealment and we received no reply from the author. 39 One trial (16.7%) gave no information regarding sequence generation or allocation concealment.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that microemulsion significantly attenuate exudation and symptoms as compared to placebo [13]. The effect of LNIT to AR using allergen of the allergen dermats phagodes prevony was found to reduce the need for nasal medications [11] and severity of AR histamine release and eosinophilic protein were reduced in nasal mucosa 4 months after treatment. There were no severe adverse effect this was found to be good alternative treatment for AR [12].…”
Section: Chemical Manufacturesmentioning
confidence: 95%
“…It was found that endoscopically nose appeared better but the symptom scores of patient did not improve. The amphotericin B solution acts as antifungal as well as "Biofilms" dysruptor [11].…”
Section: Humidification Of Nosementioning
confidence: 99%